Sociologies of New Zealand - Crothers, Charles (Sociology Transformed, 2018)
'This book provides a comprehensive survey of the discipline that relates both the successes and challenges of creating and sustaining a sociological perspective within this small semi-peripheral society.' -David Pearson, Victoria University of Wellington, New Zealand 'A thoroughly fascinating account of the growth of New Zealand Sociology which addresses the thorny question of whether there has been, or remains, a distinctive Sociology of New Zealand - a question often raised but rarely answered.' -Fran Collyer, University of Sydney, Australia This book provides the first comprehensive analysis of the various sociologies of New Zealand from the late 19th century to the present day. Opening with previously undocumented insights into the history of proto-sociology in New Zealand, the book then explores the parallel stories of the discipline both as a mainstream subject in Sociology departments and as a more diffuse 'sociology' within other university units .The rise and fall of departments, specialties and research networks is plotted and the ways in which external and internal factors have shaped these is explained. Different generations of sociologists, including many immigrants, are each shown to have left their unique mark on New Zealand sociology. The author demonstrates that the rising interest in topics specific to New Zealand has been accompanied by increasing capacities to contribute to world sociology. This book will have inter-disciplinary appeal across the social sciences and provides a valuable study of the development of sociology in a semi-peripheral country. Charles Crothers is Professor of Sociology in the Department of Social Sciences at Auckland University of Technology, New Zealand, and Senior Research Associate at the University of Johannesburg, South Africa.